Construction of a scale measuring primary teachers’ self-efficacy to teach STEAM: the STEAM-TSES - Stepanović Ilić, Ivana; Peixoto, Francisco; Dabić Boričić, Milana; Videnović, Marina; Castro Silva, Jose; Ferreira, Nadia; Monteiro, Vera (Frontiers in Education, 2025)
The STEAM-TSES was developed to measure teachers’ self-efficacy (TSE) in teaching STEAM disciplines due to the lack of instruments measuring specific TSE dimensions, especially in STEAM education. This paper presents the validation results based on a sample of 805 Portuguese and Serbian primary school teachers. The scale comprises 36 items measuring TSE related to mathematics, biology, chemistry, science, and arts, the ability to motivate students, and confidence in integrating STEAM disciplines. The measurement model tested through Exploratory Structural Equation Modeling and Confirmatory Factor Analysis showed an acceptable fit to the data, supporting the existence of nine factors: five related to TSE in teaching specific subjects, three focused on motivating students in mathematics, science, and arts, and one related to integrated teaching. The analyses show good psychometric characteristics of the STEAM-TSES, and the correlations with the TSE scale indicate the validity of distinguishing constructs associated with STEAM education.